Reformasi Administrasi Pelayanan Publik di Desa Banjar Kemuning Kecamatan Sedati Kabupaten Sidoarjo - Atyah. S, Umi; Nauval. N, Muhammad; Tegar. P, Satrio; Casmiwati, Dewi (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study aims to determine the Reform of Public Service Administration in Banjar Kemuning Village, Sedati District, Sidoarjo Regency. This study uses a qualitative descriptive approach method. The results of this study indicate that the Service in Banjar Kemuning Village has met the indicators of the theory of public service quality according to Parasuraman, Zeithaml, and Berry (1988). All services use digital, namely websites or applications. Although there are slight obstacles from the facilities and infrastructure, namely the application or website has server problems or in other words